Analysis of certain fatty acids and toxic metal bioaccumulation in various tissues of three fish species that are consumed by Turkish people - Kaya, Gokce; Turkoglu, Semra (Springer Heidelberg, 2017)
Concentrations of toxic metals (Mn, Ni, Hg, Cd, Pb, Cr) in the muscle, skin, and liver of Mugil cephalus, Mullus barbatus, and Pagellus erythrinus which were purchased in large supermarkets of Elazig, and Mullus barbatus, which were caught on the sea of A degrees skenderun Bay, Turkey, were analyzed. Fundamental analyses were carried out by inductively coupled plasma-mass spectrometry (ICP-MS) after samples were prepared by microwave digestion. Mean metal concentrations in different tissues were varied in the ranges of Cd 4-426, Cr 116-4458, Mn 141-24774, Hg 9-471, Pb 96-695, and Ni 68-6581 mu g kg(-1), for wet weight. The investigated metal bioaccumulation in the muscles of fish species, in general, was lower than those in the liver and skin. This method was verified by NCS ZC73016 chicken trace element-certified reference material analysis. In addition, fatty acids in the muscles of three fish species were analyzed. According to the gas chromatography (GC) results of fatty acids, the monounsaturated fatty acids (MUFA) were found to be between 23.76 and 31.97%. The fatty acids' polyunsaturated fatty acids (PUFA) ratio was found to be between 13.67 and 30.71% and saturated fatty acids ratios were determined in the range of 24.06-32.30%. In all fish species, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) ratio, which increase the value of these fish species, were high. These results show that these three fish species are good sources of fatty acids.
Keywords: Bioaccumulation; Fatty acids; Fish; Muscle; Skin; Liver; Toxicmetals; ICP-MS; GC